Reform Regulations And Responsibilities Of Beneficial Ownership In Limited Companies In Connection With The Crime Of Money Laundering - Saputra, Dhimas; Prasetyo, Handoyo; Wahyudi, Slamet Tri (PT. Hafasy Dwi Nawasena, 2024)
In this case, a Limited Liability Company (LLC) can be used to conceal beneficial ownership, which can be a method to cover up money laundering activities. This research aims to explore the role of beneficial ownership in limited liability companies. The research methodology is juridical-normative, employing statutory and conceptual approaches. Secondary data obtained from literature studies is utilized. The position of the beneficial owner (BO) in a limited liability company is not yet specifically regulated within the Indonesian national legal framework. Presidential Regulation Number 13 of 2018 regarding the Implementation of the Principle of Recognizing the Beneficial Owners of Corporations in the Context of Preventing and Eradicating Money Laundering and Terrorism Financing Crimes introduces the definition of a BO as an individual who is the ultimate beneficiary or holds the highest level of authority with complete control over the company. The BO's position in the company is based on their rights as outlined in Article 4 Paragraph (1) of Presidential Regulation Number 13 of 2018, which equates them to a Major Shareholder. A BO holds shares, voting rights, and profit rights exceeding 25%, which surpasses the minimum shareholding requirement for major shareholders of at least 20% in the company.